PEMANFAATAN BIJI NANGKA SEBAGAI EDIBLE FILM DENGAN PENAMBAHAN KARAGENAN TERHADAP KUAT TARIK BIODEGRADASI - nur azizah; Indang Dewata (Universitas Negeri Padang, 2021)
Edible film is a thin plastic with a thickness of less than 0,25 mm and serves to protect food products. This study aims to determine the effect of adding carrageenan to edible film made from jackfruit seed starch (Artocarpus heterophyllus) on thickness, tensile strength, biodegradation and functional group analysis using the FTIR technique. This research was conducted by varying the concentration of carrageenan used, namely 0%, 0.5%, 1%, 1.5% and 2%. Based on the results of the analysis carried out, the addition of carrageenan affects the thickness, tensile strength and biodegradation of edible films. The maximum tensile strength was found in the addition of 1.5% carrageenan, which was 13.315 MPa, while the thickness and biodegradation increased with increasing carrageenan concentration. The tensile strength and thickness values obtained on the edible film have met the JIS ZI 707 standard edible film.